2022
DOI: 10.30541/v40i4iipp.651-674
|View full text |Cite
|
Sign up to set email alerts
|

Testing Semi-strong Form Efficiency of Stock Market

Abstract: The efficient market hypothesis suggests that stock markets are “informationally efficient”. That is, any new information relevant to the market is spontaneously reflected in the stock prices. A consequence of this hypothesis is that past prices cannot have any predictive power for future prices once the current prices have been used as an explanatory variable. In other words the change in future prices depends only on arrival of new information that was unpredictable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Husain (1998,1999), Chakraborty (2006), and Ali and Akbar (2009) are a few of the studies that investigate the weak form of market efficiency in the Pakistani equity market. Ali and Mustafa (2001) examine the semistrong form of market efficiency in the Karachi Stock Exchange (KSE) by analyzing public news in two daily newspapers and the changes in trade volume and stock returns. They conclude that public information did not play an important role in the determination of stock returns since stock returns appeared more sensitive to private information.…”
Section: Dividend Announcements and Stock Returnsmentioning
confidence: 99%
“…Husain (1998,1999), Chakraborty (2006), and Ali and Akbar (2009) are a few of the studies that investigate the weak form of market efficiency in the Pakistani equity market. Ali and Mustafa (2001) examine the semistrong form of market efficiency in the Karachi Stock Exchange (KSE) by analyzing public news in two daily newspapers and the changes in trade volume and stock returns. They conclude that public information did not play an important role in the determination of stock returns since stock returns appeared more sensitive to private information.…”
Section: Dividend Announcements and Stock Returnsmentioning
confidence: 99%
“…However, the indings of these studies were mixed. The semi strong form of EMH has been tested and mixed indings were reported (Ali et al, 2001;Hussin et al, 2010;Hsu and Utami, 2016;Khan and Ikram, 2010). Likewise, previous research has tested the strong form of ef icient market hypothesis (Finnerty, 1976;Rozeff and Zaman, 1988).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Through the use of the unit root test and the GARCH (1, 1), this study showed that these markets are not weak form efficient and do not follow the RWH. Ali and Mustafa (2001), employing the use of correlation coefficient of successive returns, averages, logarithms and regression analysis on daily price data of listed equities, tested this hypothesis in the Pakistani capital market and discovered that information collectively had an effect on stock prices, both negatively and positively. Lo and Mackinlay (1988) variance tests came up with inadequate inferences about the stock price index following a random walk at a fixed significance level.…”
Section: Related Literaturementioning
confidence: 99%